Analisis kandungan terhadap drama adaptasi Korea di Malaysia - Nazra Aliff Nazri,; Abdul Latiff Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Television has been an effective medium of communication in delivering information as well as spreading one’s culture. Among the television programmes that are favored by the community are drama series from Korea which provide access in connecting Malaysian youth and the Hallyu culture. Nevertheless, the presence of Hallyu in the local context gave quite a negative impact especially in matters relating to youth, culture and religion. Nowadays, with the Hallyu culture gaining popularity, more dramas derived from Korea have been widely adapted into local context. Noticeable critics and culture’s polemic between Malaysia and Korea have prompted this research to discover more about culture presented through Korean adaptation drama 'Alamatnya Cinta' (Full House) and 'My Coffee Prince' (The 1st Shop of Coffee Prince) based on Cultural Norms Theory by Melvin DeFleur (1970). A content analysis was done on the adapted dramas to understand the cultural representation of Korea into the Malaysian version. The data have shown that the prominence of Korean culture in adaptations drama has been watered down compared to the Malaysian version of the drama. This indicates that the idea of Hallyu being a threat to the local culture is not substantial. The Malaysian version would express the Korean culture in Malaysian context thus using local references and indicators in trying to comply with the Korean version. All in all, the presence of Korean adaptation dramas in Malaysia is a good initiative especially in preserving the elements of Malay culture though the original content may differ.